Structural basis of tail-anchored membrane protein biogenesis by the GET insertase complex - McDowell, Melanie; Heimes, Michael; Fiorentino, Francesco; Mehmood, Shahid; Farkas, Ákos; Coy-Vergara, Javier; Wu, Di; Bolla, Jani Reddy; Schmid, Volker; Heinze, Roger J.; Wild, Klemens; Flemming, Dirk; et al. (Molecular cell, 2020)
Membrane protein biogenesis faces the challenge of chaperoning hydrophobic transmembrane helices for faithful membrane insertion. The guided entry of tail-anchored proteins (GET) pathway targets and inserts tail-anchored (TA) proteins into the endoplasmic reticulum (ER) membrane with an insertase (yeast Get1/Get2 or mammalian WRB/CAML) that captures the TA from a cytoplasmic chaperone (Get3 or TRC40, respectively). Here, we present cryo-electron microscopy reconstructions, native mass spectrometry, and structure-based mutagenesis of human WRB/CAML/TRC40 and yeast Get1/Get2/Get3 complexes. Get3 binding to the membrane insertase supports heterotetramer formation, and phosphatidylinositol binding at the heterotetramer interface stabilizes the insertase for efficient TA insertion in vivo. We identify a Get2/CAML cytoplasmic helix that forms a “gating” interaction with Get3/TRC40 important for TA insertion. Structural homology with YidC and the ER membrane protein complex (EMC) implicates an evolutionarily conserved insertion mechanism for divergent substrates utilizing a hydrophilic groove. Thus, we provide a detailed structural and mechanistic framework to understand TA membrane insertion.